Full Simulation Of Cycle Time Using Talpac Software At Lafarge Kanthan Quarry - Meor Akil Julnasir, Nurwahidah (Universiti Sains Malaysia, 2018)
Cycle time of loading and hauling equipment for quarrying operations has a significant impact on quarry productivity. The most typical materials handling is by truck and loader combination. Operation of materials handling is one of the important key element that helps to reduce or vice versa the cost of mineral production. This study focused on developing a full simulation that can be used during the calculation of loader productivity as well as fleet production management for a quarry. By comparing different types of loading methodologies, quarry operators can select the best method that yield the highest productivity. In referral to the case study of Lafarge Kanthan Cement Quarry, this simulation has proved to be an important tool in determining the best loading methodology by considering both cycle time and on-site data including environmental components and haul road conditions together with cycle time observations were also collected periodically throughout the study duration. Results indicate that full truck for bucket passes and single-sided of truck positioning for loading methodology yield the highest productivity with shortest cycle time. Roster, speed, driver visibility, safety and traffic management can significantly impact the dump truck cycle time. The significant contribution of this research is the identification and analysis of statistical relationship of variables within the cycle time.